Treatment with chloramphenicol of acute bartonellosis (Carrion's disease) in the period beginning - Cuadra, Manuel (1957)
Four patients attacked Bartonellosis acute (severe fever of Carrion), at its start (anemia and low grade fever bacillary forms of Bartonella bacilliformis) were treated with chloramphenicol. Chloramphenicol was effective in all cases. The fever fell between 24 and 48 hours; the bartonellae disappeared between 24 and 48 hours. As the treatment has been carried out in a period of the disease onset demonstrative results have great value; did not occur severe anemia usually occurs in untreated cases. Relapse occurred in one case; She was successfully treated with the same antibiotic. Chloramphenicol efficacy against Bartonella bacilliformis and against Salmonella bacteria, which often produce serious secondary infections, often fatal course, make the best antibiotic chloramphenicol for the treatment of acute Bartonellosis.